Measuring the Local Twist Angle and Layer Arrangement in Van der Waals Heterostructures. Issue 12 (19th August 2018) - de Jong, Tobias A.; Jobst, Johannes; Yoo, Hyobin; Krasovskii, Eugene E.; Kim, Philip; van der Molen, Sense Jan
Abstract : The properties of Van der Waals (VdW) heterostructures are determined by the twist angle and the interface between adjacent layers as well as their polytype and stacking. Here, the use of spectroscopic low energy electron microscopy (LEEM) and micro low energy electron diffraction (µLEED) methods to measure these properties locally is described. The authors present results on a MoS2 /hBN heterostructure, but the methods are applicable to other materials. Diffraction spot analysis is used to assess the benefits of using hBN as a substrate. In addition, by making use of the broken rotational symmetry of the lattice, the cleaving history of the MoS2 flake is determined, that is, which layer stems from where in the bulk. Abstract : Advanced low‐energy electron microscopy techniques are used to unravel important properties of Van der Waals heterostacks: using local diffraction spectroscopy, the stacking order, twist angle, and local orientation of the topmost layer are determined.